Influence of Choice of Curing Method on the Dielectric, Thermal and Mechanical Properties of Geopolymer Mortar-Natural Rubber Latex (GM-NRL) Blends - Saysunee Jumrat (Faculty of Science, Chiang Mai University, 2020)
Chiang Mai Journal of Science